PROGRESS OF THE BUREAU FOR PLACEMENTS. - Niseley, W. W. (The Accounting Review, 1928)
The author in the article discusses the progress of the Bureau of Placements of the American Institute of Accountants as he received a number of letters from teachers of accounting which indicate that some are not in entire sympathy with the work of the Bureau. The author attempts to give first a brief summary of the purpose for which the Bureau of Placements was organized and of what it has accomplished to date. He then attempts to answer the questions raised in the letters received from accounting teachers. However, the author also notifies that these comments do not represent the official opinion of the American Institute of Accountants nor of the Committee for Placements, and should be regarded as his personal comments. In a letter to the author, an accounting teacher objects to the statement by the author that "It has been the experience of accountancy firms that men graduated from cultural courses in the liberal arts and science develop quite as rapidly as men who have devoted most of their time to technical accounting study." The author clarifies that this sentence does not refer to men who have had the combined cultural and technical study previously referred to. This statement, moreover, was intended to encourage the academic man with desirable natural qualifications to make an application.